2009
DOI: 10.1002/rcm.4103
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput approaches towards the definitive identification of pharmaceutical drug metabolites. 2. An example of how unexpected dissociation behaviour could preclude correct assignment of sites of metabolism

Abstract: The low-energy collision-induced dissociation product ion spectra of protonated beta-blockers reveal an analogy to fragmentation under electron ionisation conditions", J. Mass Spectrom. 2011Spectrom. , 1182Spectrom. -1185 S.W. Holman, P. Wright, N.J. Wells and G.J. Langley, "Evidence for site-specific intra-ionic hydrogen/deuterium exchange in the low-energy collision-induced dissociation product ion spectra of protonated small molecules generated by electrospray ionisation" J. Mass Spectrom. 2010, 45, 347-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Indeed, it is possible that protonation occurs at all suitable sites, but with lower abundance for the less stable protonated species. The inference that protonation may result in a mixture of ionised species is supported in two recent papers both of which report that two isobaric ions23, 24 in the same spectra can only have been formed from precursor ions protonated on different atoms. It should be noted that that the fragmentation reported in the paper by Holman et al ,23 resulting in isobaric product ions, would also be observed if the precursor ion was protonated at a single site during ionisation then underwent proton migration during CID.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, it is possible that protonation occurs at all suitable sites, but with lower abundance for the less stable protonated species. The inference that protonation may result in a mixture of ionised species is supported in two recent papers both of which report that two isobaric ions23, 24 in the same spectra can only have been formed from precursor ions protonated on different atoms. It should be noted that that the fragmentation reported in the paper by Holman et al ,23 resulting in isobaric product ions, would also be observed if the precursor ion was protonated at a single site during ionisation then underwent proton migration during CID.…”
Section: Discussionmentioning
confidence: 97%
“…The inference that protonation may result in a mixture of ionised species is supported in two recent papers both of which report that two isobaric ions23, 24 in the same spectra can only have been formed from precursor ions protonated on different atoms. It should be noted that that the fragmentation reported in the paper by Holman et al ,23 resulting in isobaric product ions, would also be observed if the precursor ion was protonated at a single site during ionisation then underwent proton migration during CID. However, the study by Kaufmann et al 24 provides experimental evidence, including differing effects of cone voltage on the sampling of the isobaric [M+H] + ions, that formation of a mixture of singly charged species during ionisation does occur.…”
Section: Discussionmentioning
confidence: 97%
“…Other groups have also reported that precursor ions appear to be a mixture of ions protonated at different positions. Two isobaric ions observed in an MS/MS spectrum could only be assigned if they are derived from precursor ions protonated at different sites, giving rise to different product ions . Kaufmann reported that a mixture of singly charged difloxacin species were formed in the source .…”
Section: Resultsmentioning
confidence: 99%
“…Two isobaric ions observed in an MS/MS spectrum could only be assigned if they are derived from precursor ions protonated at different sites, giving rise to different product ions. [30] Kaufmann reported that a mixture of singly charged difloxacin species were formed in the source. [31] Komaromi et al observed that N-acetyl-O-methoxyproline exhibits two distinct fragmentation pathways indicative of the coexistence of several protonated forms.…”
Section: Prediction Of Bond Cleavage On Basis Of Calculated Bond Elonmentioning
confidence: 99%
“…A number of recent reviews have discussed in detail the role of bioanalysis in metabolite identification [8,61,[69][70][71]. A consequence of recent advances to address high-throughput technology for screening the metabolic liability of compounds is the demand for more rapid methods for metabolite identification [72][73][74]. The bioanalytical approaches which appear most amenable to support these demands utilise UPLC and HILIC [32,41,51], whose applications have already been presented earlier in the context of metabolic stability studies.…”
Section: Mass Spectrometry In Studies Of Drug Biotransformationmentioning
confidence: 99%